STOP-Bang Questionnaire in Patients with Rapid Eye Movement Sleep Behavior Disorder - Ki-Hwan Ji; Mi-Ri Kang (Sleep Medicine Research, 2017)
Background and Objective The snoring, tiredness, observed apnea, and high blood pressure– body mass index, age, neck circumference, and gender (STOP-Bang) questionnaire is known as a simple but useful tool for the diagnosis of high-risk obstructive sleep apnea (OSA). However, the utility of STOP-Bang questionnaire in rapid eye movement (REM) sleep behavior disorder (RBD) populations is not validated. This study aimed to determine the diagnostic value of the STOP-Bang questionnaire in patients with RBD at high risk for OSA. Methods We collected data from 65 consecutive patients who were diagnosed with RBD in a tertiary sleep center (20 women; mean age, 64.3 ± 12.5 years). All the patients visited sleep center with complaints of abnormal behavior during sleep, and underwent testing with STOP-Bang questionnaire and polysomnography. The diagnosis of RBD was based on the International Classification of Sleep Disorders, second edition. We diagnosed OSA when apnea-hypopnea index (AHI) was at least 5/h. The receiver operating characteristic (ROC) curves were plotted. Results The mean AHI was 18.2 ± 16.5/h, and 75.4% (n = 49) had an AHI ≥ 5. The STOP-Bang (threshold ≥ 3) identified 70.7% of patients as high risk for OSA, and sensitivity, specificity, positive and negative predictive values were 81.6, 62.5, 87, and 52.6%, respectively. The area under the ROC curve (AUC) was 0.79 (p < 0.001). The STOP (threshold ≥ 2) identified 70.7% of patients at high risk for OSA, and sensitivity, specificity, positive and negative predictive values were 75.5, 87.5, 94.9, and 53.8%, respectively. The AUC was 0.86 (p < 0.001). A pairwise comparison of ROC curve between STOP-Bang and STOP was insignificant (p = 0.145). Conclusions In RBD population, the STOP-Bang or STOP questionnaire is a useful screening tool to identify patients at high risk for OSA.